DELEGATED ACTS AND IMPLEMENTING ACTS – NEW LEGAL ACTS OF THE EUROPEAN UNION - Oana-Mihaela SALOMIA (Challenges of the Knowledge Society)
The Lisbon Treaty has introduced a new generic title – “legal acts” referring to the secondary European Union Law acts (art. 288-289 TFEU), compulsory or not, but also to the new delegated acts and implementing acts. These new acts could be adopted by the European Commission which generally has the legislative initiative power and, in special cases, by the Council, in accordance with the art. 290 TFEU and art. 291 TFEU. It is obvious that new competences are allowed to the European Commission which is in charge with the application and protection of the European Union law on the basis of the art. 17 TEU; the power of the Commission to adopt compulsory acts, even that they are not legislative, could be used in order to increase the enforcement procedures against the Member States which do not respect the European Union law. This new category of legal acts are adopted on the basis of the specific procedure and they could be entitled such as the "classic" secondary EU law acts, namely regulations or directives. In conclusion, this new category of acts could represent an appropriate instrument used by the Commission ensuring the unitary application of the EU law and its respect by the Member States.